Aerosol characteristics in north-east India using ARFINET spectral optical depth measurements. (January 2016) - Pathak, B.; Subba, T.; Dahutia, P.; Bhuyan, P.K.; Moorthy, K. Krishna; Gogoi, M.M.; Babu, S. Suresh; Chutia, L.; Ajay, P.; Biswas, J.; Bharali, C.; Borgohain, A.; et al.
Abstract: Four years (2010–2014) of spectral aerosol optical depth (AOD) data from 4 Indian Space Research Organisation's ARFINET (Aerosol Radiative Forcing over India) stations (Shillong, Agartala, Imphal and Dibrugarh) in the North-Eastern Region (NER) of India (lying between 22–30°N and 89–98°E) are synthesized to evolve a regional aerosol representation, for the first time. Results show that the columnar AOD (an indicator of the column abundance of aerosols) is highest at Agartala (0.80 ± 0.24) in the west and lowest at Imphal (0.59 ± 0.23) in the east in the pre-monsoon season due to intense anthropogenic bio-mass burning in this region aided by long-range transport from the high aerosol laden regions of the Indo-Gangetic Plains (IGP), polluted Bangladesh and Bay of Bengal. In addition to local biogenic aerosols and pollutants emitted from brick kilns, oil/gas fields, household bio-fuel/fossil-fuel, vehicles, industries. Aerosol distribution and climatic impacts show a west to east gradient within the NER. For example, the climatological mean AODs are 0.67 ± 0.26, 0.52 ± 0.14, 0.40 ± 0.17 and 0.41 ± 0.23 respectively in Agartala, Shillong, Imphal and Dibrugarh which are geographically located from west to east within the NER. The average aerosol burden in NER ranks second highest with climatological mean AOD 0.49 ± 0.2 next to the Indo-Gangetic Plains where the climatological mean AOD is 0.64 ± 0.2 followed by the South and South-East Asia region. Elevated aerosol layers are observed over the eastern most stations Dibrugarh and Imphal, while at the western stations the concentrations are high near the surface. The climate implications of aerosols are evaluated in terms of aerosol radiative forcing (ARF) and consequent heating of the atmosphere in the region which follows AOD and exhibit high values in pre-monsoon season at all the locations except in Agartala. The highest ARF in the atmosphere occurs in the pre-monsoon season ranging from 48.6 Wm −2 in Agartala to 25.1 Wm −2 in Imphal. Winter radiative forcing follows that in pre-monsoon season at these locations. The heating rate is high at 1.2 K day −1 and 1.0 K day −1 over Shillong and Dibrugarh respectively in this season. However, Agartala experiences higher surface forcing (−56.5 Wm −2 ) and consequent larger heating of the atmosphere of 1.6 K day −1 in winter. Highlights: Aerosol characteristics in the North-East India exhibits a west to east gradient. Aerosol loading in the North-East India ranks second highest in Asia next to IGP. Surface forcing and consequent atmospheric heating exceeds many locations of India. Elevated aerosol layers are caused by upper air transportation.